Constraints on axion-like particles from X-ray observations of NGC1275 - Berg, M; Conlon, J; Day, F; Jennings, N; Krippendorf, S; Powell, A; Rummel, M (IOP Publishing, 2017)
Axion-like particles (ALPs) can induce localized oscillatory modulations in the spectra of photon sources passing through astrophysical magnetic fields. Ultra-deep Chandra observations of the Perseus cluster contain over 5× {10}5 counts from the active galactic nucleus (AGN) of the central cluster galaxy NGC1275 and represent a data set of extraordinary quality for ALP searches. We use this data set to search for X-ray spectral irregularities from the AGN. The absence of irregularities at the { O }(30 % ) level allows us to place leading constraints on the ALP-photon mixing parameter gaγ γ ≲ 1.4{--}4.0× {10}-12 GeV-1 for ma≲ {10}-12 {eV}, depending on assumptions on the magnetic field realization along the line of sight.